Female Empowerment and Leadership in Black Panther: Wakanda Forever: A Content Analysis of Female Characters - Irwan, Irwan; Rosalinah, Yanti (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
This study explores the representation of female empowerment and leadership in Black Panther: Wakanda Forever (2022) through a qualitative content analysis framed by postcolonial feminist theory. The film marks a transformative moment in the Marvel Cinematic Universe (MCU) by centering women as political, intellectual, and emotional leaders within an Afrocentric context. Focusing on four main female characters—Queen Ramonda, Princess Shuri, General Okoye, and Nakia—the analysis examines verbal, visual, and narrative elements to uncover how the film constructs multidimensional models of womanhood and power. Findings reveal that Wakanda Forever challenges patriarchal and Western-centric portrayals of leadership by depicting empowerment as collective, relational, and rooted in moral integrity and cultural identity. Each character represents a distinct form of leadership—wisdom, innovation, discipline, and compassion—that together articulate an inclusive feminist vision. Through symbolic cinematography and dialogue, the film reframes heroism as healing and collaboration rather than domination. Ultimately, Wakanda Forever serves as both a cinematic and ideological statement that redefines gender representation, promoting intersectionality, empathy, and transformative leadership in contemporary popular culture.